Ajoene, a Sulfur-Rich Molecule from Garlic, Inhibits Genes Controlled by Quorum Sensing - Jakobsen, Tim Holm (American Society for Microbiology, 2012)
In relation to emerging multiresistant bacteria, development of antimicrobials and new treatment strategies of infections should be expected to become a high-priority research area. Quorum sensing (QS), a communication system used by pathogenic bacteria like Pseudomonas aeruginosa to synchronize the expression of specific genes involved in pathogenicity, is a possible drug target. Previous in vitro and in vivo studies revealed a significant inhibition of P. aeruginosa QS by crude garlic extract. By bioassay-guided fractionation of garlic extracts, we determined the primary QS inhibitor present in garlic to be ajoene, a sulfur-containing compound with potential as an antipathogenic drug. By comprehensive in vitro and in vivo studies, the effect of synthetic ajoene toward P. aeruginosa was elucidated. DNA microarray studies of ajoene-treated P. aeruginosa cultures revealed a concentration-dependent attenuation of a few but central QS-controlled virulence factors, including rhamnolipid. Furthermore, ajoene treatment of in vitro biofilms demonstrated a clear synergistic, antimicrobial effect with tobramycin on biofilm killing and a cease in lytic necrosis of polymorphonuclear leukocytes. Furthermore, in a mouse model of pulmonary infection, a significant clearing of infecting P. aeruginosa was detected in ajoene-treated mice compared to a nontreated control group. This study adds to the list of examples demonstrating the potential of QS-interfering compounds in the treatment of bacterial infections.